If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-5) = b + (-11) -5 = b + (-11) -5 = b + -11 Reorder the terms: -5 = -11 + b Solving -5 = -11 + b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-1b' to each side of the equation. -5 + -1b = -11 + b + -1b Combine like terms: b + -1b = 0 -5 + -1b = -11 + 0 -5 + -1b = -11 Add '5' to each side of the equation. -5 + 5 + -1b = -11 + 5 Combine like terms: -5 + 5 = 0 0 + -1b = -11 + 5 -1b = -11 + 5 Combine like terms: -11 + 5 = -6 -1b = -6 Divide each side by '-1'. b = 6 Simplifying b = 6
| -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 | | -0.9+z=0.075 | | 69=3u | | 0.06x+0.02(7-x)= | | 6p+4= | | 8-3=3x-2-8x | | 4+e=8+(-2) | | 3(5x+3)=6x-3+5x+3 | | 10b+50=30 | | 10x^2+13x+-9=0 | | -(x+5)=-1 | | 5h-12=4h+6 | | 3(-4+3)=2 | | 8x^4-42x^2=0 | | 2(1[3u-7]1)=16 |